2012
DOI: 10.3390/ijms131013691
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association of Estrogen Receptor Alpha Gene Polymorphisms with Cardiorespiratory and Metabolic Variables in Young Women

Abstract: This study examined the association of estrogen receptor alpha gene (ESR1) polymorphisms with cardiorespiratory and metabolic parameters in young women. In total, 354 healthy women were selected for cardiopulmonary exercise testing and short-term heart rate (HR) variability (HRV) evaluation. The HRV analysis was determined by the temporal indices rMSSD (square root of the mean squared differences of successive R–R intervals (RRi) divided by the number of RRi minus one), SDNN (root mean square of differences fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…It should be emphasized that several factors may change the HR in women menstrual cycle. Because of this, all measurements were taken during the follicular phase of the menstrual cycle or in the phase of high hormonal concentration in women who used some type of contraceptive (Rebelo et al 2012), since this is the phase of greater hormonal stability and HRV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be emphasized that several factors may change the HR in women menstrual cycle. Because of this, all measurements were taken during the follicular phase of the menstrual cycle or in the phase of high hormonal concentration in women who used some type of contraceptive (Rebelo et al 2012), since this is the phase of greater hormonal stability and HRV.…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamic, autonomic, and glycemic parameters were all measured during either the follicular phase of the menstrual cycle or the phase of high hormonal concentration in women using contraceptive (Rebelo et al. ). The percentage of fat, along with weight, height, glycemic, blood pressure, quality of life (SF‐36) and perceived stress level (PSS‐10) were assessed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we found no association of SNPs in the ESR1 gene with MetS; these results coincide with those reported by Goulart et al, where they found no relation of SNPs in ESR1 and ESR2 genes with MetS in Caucasian postmenopausal women ( n = 532) [ 21 ]. However, in the study conducted in young women ( n = 354) by Rebelo et al , they found no association between rs2234693 and rs9340799 SNPs with metabolic variables (total cholesterol, HDL-c, LDL-c, and triglycerides) [ 22 ]. Moreover Gallagher et al reported the association of rs9340799 polymorphism in the ESR1 gene with MetS, and the C allele of rs2234693 with reduced insulin sensitivity in African American families ( n = 548) [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The amplicons were subjected to electrophoresis on a 10% acrylamide gel and stained with ethidium bromide. Genotyping quality control was performed as described in detail elsewhere [26]. All genotypes were determined by two independent technicians, the results were entered in the database in duplicate, and 10% of the samples were randomly reanalyzed.…”
Section: Methodsmentioning
confidence: 99%